ASEAN Community: Strengthening Spirit of Unity In Diversity Through Political Communication - Kartika Giri, Setyasih Harini & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Indonesia is a large archipelago that contains population numbering more than 250million people, a number that makes Indonesia one of the most populous countriesin the world. These large number imply that significant culture, ethnic, religiousand linguistic diversity. Indonesias national spirit Bhinekka Tunggal Ika (Unity inDiversity) refers to the variety in the countrys internal composition but alsoindicates that despite all differences in its multicultural society there is a true senseof unity (Indonesianness) among the people of Indonesia. Strengthening this spiritthrough political communication is very important in ASEAN Community.ASEAN Community as product of new regionalism give an opportunity for eachcountry to promote its potency narrowing development gap. One of the pillars ofASEAN Community, ASEAN Socio-Culture Community can be an opportunity fornational identity of Indonesia. As an opportunity, culture, ethnic, religious andlinguistic diversity of Indonesia that be strengthened by state philosophy Pancasilaas means national identity. Political communication is an integral parts ofIndonesia people daily life that crucial influence on the political socialisation ofthe individual. Political communication is a one way to strengthen relation betweengovernment and people. Indonesia, need to promote unity in diversity amongcountries in Southeast Asia. Its consequently, first, developing of modern relationsand coomunications, specially, in ASEAN Community should be determined bythe rise of communication and information technology namely social media. Thenext consequently it could be mean to fulfill national interest in politic, economic,and security.Key words: unity in diversity, ASEAN Community, social media